Assessment of proliferation in breast cancer: cell cycle or mitosis? An observational study. Issue 6 (20th September 2021) - Lashen, Ayat G; Toss, Michael S; Katayama, Ayaka; Gogna, Rajan; Mongan, Nigel P; Rakha, Emad A
Abstract : Background and aims: Proliferation is an important indicator of breast cancer (BC) prognosis, but is assessed using different approaches. Not all cells in the cell cycle are committed to division. This study aimed to characterise quantitative differences between BC cells in the cell cycle and those in mitosis and assess their relationship with other pathological parameters. Methods and results: A cohort of BC sections ( n  = 621) was stained with haematoxylin and eosin and immunohistochemistry for Ki‐67. The proportion of mitotic cells and Ki‐67‐positive cells was assessed in the same areas. The Cancer Genome Atlas (TCGA) BC cohort was used to assess MKI‐67 transcriptome level and its association with the mitotic counts. The mean proportion of BC cells in the cell cycle was 24% (range = 1–90%), while the mean proportion of BC cells in mitosis was 5% (range = 0–73%). A low proportion of mitoses to whole cycling cells was associated with low histological grade tumours and the luminal A molecular subtype, while tumours with a high proportion of mitoses to the overall cycling cells were associated with triple‐negative subtype, larger tumour size, grade 3 tumours and lymph node metastasis. The high mitosis/low Ki‐67‐positive cells tumours showed a significant association with variables of poor prognosis, including high‐grade and triple‐negative subtypes. Conclusion: The proportion of BC cells in the cell cycle and mitosis is variable. We show that not only the number of cells in the cell cycle or mitosis, but also the difference between them, provides valuable information on tumour aggressiveness. Abstract :